Penerapan Aplikasi Monitoring Peminjaman Barang sebagai Solusi Manajemen Aset pada Lingkungan Masyarakat - Anis Choirunnisa; Dera Susilawati; Adik Susilo Wardoyo; Ferdinand Febriansyah; Najwan Caesar Firstiansyah (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
This community service activity aims to implement a web-based item borrowing monitoring application as an alternative solution for asset management in a village environment. Common problems encountered in village asset management include manual borrowing records, unstructured documentation, difficulties in tracking the status of borrowed items, and an increased risk of delayed returns and asset loss. The implementation stages consist of observation and interviews to identify user requirements, system design with role-based access for Admin and Borrower, application implementation, user training for village officials and community members, and pilot testing during asset borrowing activities. The developed application is equipped with features such as item inventory management, borrowing and return transaction records, real-time monitoring of borrowing status, user activity history, and report generation. The implementation results indicate that the application improves the organization of borrowing administration, provides clearer information on item status, and accelerates data retrieval compared to the manual system. In addition, borrowing records are well documented, supporting transparency and accountability in village asset management. Therefore, the implementation of a web-based item borrowing monitoring application is considered effective in enhancing the efficiency and effectiveness of asset management in village communities.